QUALITY ASSESSMENT AND QUANTIFICATION OF GENISTEIN IN DIETARY SUPPLEMENTS BY HIGH-PERFORMANCE LIQUID CHROMATOGRAPHY, QUANTITATIVE NUCLEAR MAGNETIC RESONANCE, AND TWO-DIMENSIONAL DIFFUSION ORDERED SPECTROSCOPY 1H - IOANNA, VLACHOU; IOANNIS, PAPASOTIRIOU (Asian Journal of Pharmaceutical and Clinical Research, 2020)
Objective: The aim of the present study is to analyze four herbal dietary supplements containing genistein by liquid chromatography, quantitative nuclear magnetic resonance (qNMR), and diffusion ordered spectroscopy (DOSY) 1H NMR. Methods: Quantification of the active ingredient, genistein, is carried out by high-performance liquid chromatography (HPLC) and qNMR. Two-dimensional (2D) DOSY NMR also allows the qualitative analysis of the samples with the detection of active ingredient and excipients present in the formulations. Results: The validated HPLC and qNMR methods showed that all four supplements contain genistein in different amounts, and 2D DOSY NMR provides a clear image of all ingredients in the formulations. Conclusion: The use of the three techniques provides detailed information on each product and its contents, and all of them are currently used for the quality control of natural supplements by our laboratory.